Increasing reciprocal social interactions using collaborative art activities: An intervention for children with complex communication needs and their peers. (4th March 2022) - Boster, Jamie B.; McCarthy, John W.; Benigno, Joann P.; Ottley, Jennifer; Spitzley, Alyson M.; Montgomery, James
Abstract: Purpose: Children with complex communication needs who require augmentative and alternative communication (AAC) strategies to communicate have difficulty participating in interactions with their peers. Integrating a collaborative learning framework with art activities may facilitate social interactions between children with complex communication needs and their peers. Method: A single-subject withdrawal design was utilised to examine the impact of collaborative art activities on reciprocal social interactions between 2 dyads of participants with complex communication needs and their same-age peers. Additional dependent variables included the roles of participants with complex communication needs in interactions (initiator or responder), AAC modalities (unaided, aided, natural speech), and engagement. Result: Tau-U calculations for Dyad 1 demonstrated 64% improvement from baseline, indicating moderate effects with the collaborative art activity (Intervention One) and 100% improvement, indicating strong effects following the activity enhanced with photography (Intervention Two). Dyad 2 demonstrated 100% improvement from baseline following Intervention One and 96% improvement following Intervention Two, indicating strong effects. Conclusion: Both collaborative art activities demonstrated potential for facilitating social interactions for children with complex communication needs and their peers.